Heterologous expression and activity verification of ornithine decarboxylase from a wild strain of Shewanella xiamenensis - Liu, Chang; Wang, Guiyuan; Han, Xiangning; Cao, Limin; Wang, Kaiqiang; Lin, Hong; Sui, Jianxin (Frontiers in Microbiology, 2022)
Shewanella xiamenensis is widely found in spoilage fish, shrimp and other seafoods. Under suitable conditions, ornithine can be synthesized into putrescine, which may spoil food or endanger health. Our research used a wild strain of Shewanella xiamenensis isolated from “Yi Lu Xian” salted fish (a salting method for sea bass) as a research object. According to the database of National Center of Biotechnology Information (NCBI), the target ornithine decarboxylase (ODC) gene SpeF was successfully amplified using the wild strain of Shewanella xiamenensis as the template. Sequencing alignment showed that the SpeF of the wild strain had more than 98% homology compared with the standard strain. The amino acid substitution occurred in the residues of 343, 618, 705, and 708 in the wild strain. After optimizing the expression conditions, a heterologous expression system of ODC was constructed to achieve a high yield of expression. The amount of 253.38 mg of ODC per liter of LB broth was finally expressed. High performance liquid chromatography (HPLC) and subsequent ODC activity verification experiments showed that hetero-expressed ODC showed a certain enzyme activity for about 11.91 ± 0.38 U/mg. Our study gives a new way to the development of a low-cost and high-yield strategy to produce ODC, providing experimental materials for further research and elimination of putrescine in food hazards.